Evidence of gene flow between transgenic and non-transgenic maize in Colombia (2015)
Maize (Zea mays) is an important crop worldwide and is essential for industry. Many transgenic cultivars of maize have been developed over the years from this species, producing cultivars resistant to herbicides and insects, among other things. However, little is known about the gene flow processes that affect maize fields in Colombia, which is near the center of diversity for cultivated maize. We analyzed the gene flow phenomenon of 60 randomly chosen plots of maize, including farmer field landraces or other conventional varieties such as non-transgenic hybrids in Valle de San Juan (Colombia) using Inmunostrip®, PCR and ELISA tests on leaves (seed gene flow) and seeds (pollen gene flow). More than 88% of the plots were positive with the Inmunostrip® and PCR tests (35S promoter, Nos terminator and cry1F gene), using the leaves, while the remaining seven plots (12%) were positive for transgenic sequences in the seeds. The results indicated a significant level of overall transgene existence, which is consistent with gene flow from transgenic events. All of the field types (conventional maize, buffer zones, refuge, and Colombian landraces) showed evidence of a transgene presence. There are many problems that could increase the gene flow potential in Valle de San Juan, such as little respect for regulations (Colombian Decree 4525 on transgenic crops and biosafety), distance between transgenic and non-transgenic maize or use of refuge and/or buffer zones, high seed reuse and exchange and low technical assistance. Every policy decision must be made in light of scientific standards of judgment.